2018
DOI: 10.1038/s41598-018-28927-4
|View full text |Cite
|
Sign up to set email alerts
|

Predator odour but not TMT induces 22-kHz ultrasonic vocalizations in rats that lead to defensive behaviours in conspecifics upon replay

Abstract: Predator odours induce defensive behaviour in prey animals such as rats. The present study investigated (1) whether laboratory rats exposed to predator odours emit 22-kHz calls which may have an alarming function and (2) whether playback of such calls induces behavioural changes in conspecifics. For this, Sprague-Dawley rats were exposed to samples of fox and lion urine, as well as to the synthetic predator odour TMT. Despite that all odours induced defensive behaviour, only predator urine samples but not TMT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 67 publications
0
51
2
Order By: Relevance
“…an aggressive intruder; , though the nuance and meaning of these are not yet well characterized. Conversely, rats reliably emit 22kHz USVs across a variety of fearful and anxiety-provoking situations, some of which include: restraint stress (Reed et al, 2013), swim stress (Drugan et al, 2013), chronic variable stress (Mällo et al, 2009), predator odor/exposure (Blanchard et al, 1991;Fendt et al, 2018), social defeat (Kaltwasser, 1990;Tornatzky and Miczek, 1994;Kroes et al, 2007), drug withdrawal (Vivian et al, 1994;Covington and Miczek, 2003;Williams et al, 2012;Berger et al, 2013), and footshock (De Vry et al, 1993;Wöhr et al, 2005). Indeed, 22kHz USV emissions are thought to serve as alarm calls capable of warning conspecifics of possible danger and/or aversive situations (Blanchard et al, 1991;Litvin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…an aggressive intruder; , though the nuance and meaning of these are not yet well characterized. Conversely, rats reliably emit 22kHz USVs across a variety of fearful and anxiety-provoking situations, some of which include: restraint stress (Reed et al, 2013), swim stress (Drugan et al, 2013), chronic variable stress (Mällo et al, 2009), predator odor/exposure (Blanchard et al, 1991;Fendt et al, 2018), social defeat (Kaltwasser, 1990;Tornatzky and Miczek, 1994;Kroes et al, 2007), drug withdrawal (Vivian et al, 1994;Covington and Miczek, 2003;Williams et al, 2012;Berger et al, 2013), and footshock (De Vry et al, 1993;Wöhr et al, 2005). Indeed, 22kHz USV emissions are thought to serve as alarm calls capable of warning conspecifics of possible danger and/or aversive situations (Blanchard et al, 1991;Litvin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, male rats are studied 51 because they express a higher frequency of social play and engage in rougher defense tactics than females. 59,60 In contrast, 50-kHz USV are believed to reflect a positive affective state ("rat laughter"), 61 as they are emitted in appetitive situations, with particularly high emission rates during and in anticipation of roughand-tumble play [62][63][64] or when social play is mimicked through an experienced human experimenter by tickling. 55 Acoustic communication is another prominent element of the rat social behavior repertoire.…”
mentioning
confidence: 99%
“…They serve an alarm function and induce behavioral inhibition in the recipient rat. 59,60 In contrast, 50-kHz USV are believed to reflect a positive affective state ("rat laughter"), 61 as they are emitted in appetitive situations, with particularly high emission rates during and in anticipation of roughand-tumble play [62][63][64] or when social play is mimicked through an experienced human experimenter by tickling. [65][66][67][68] Interestingly, we recently found the emission of 50-kHz USV to be strongly affected by partial Cacna1c depletion.…”
mentioning
confidence: 99%
“…Thus, innate fear responses to TMT are nevertheless mediated by olfaction, not by nociception. More recently, Fendt et al (2018) showed that natural predator odor of fox urine elicited 22 kHz alarming calls in Sprague-Dawley rats. However, the researchers failed to observe such ultrasonic vocalizations in response to TMT exposure (Fendt et al, 2018).…”
Section: Fox Predator Odorsmentioning
confidence: 99%